In Vitro Labeling of Hydroxyapatite Minerals by an Engineered Protein - Yuca, Esra; Karatas, Ayten Yazgan; Seker, Urartu Ozgur Safak; Gungormus, Mustafa; Dinler-Doganay, Gizem; Sarikaya, Mehmet; Tamerler, Candan (WILEY, 2011)
Biological and biomimetic synthesis of inorganics have been a major focus in hard tissue engineering as well as in green processing of advanced materials. Among the minerals formed by organisms, calcium phosphate mineralization is studied extensively to understand the formation of mineral-rich tissues. Herein, we report an engineered fusion protein that not only targets calcium phosphate minerals but also allows monitoring of biomineralization. To produce the bi-functional fusion protein, nucleotide sequence encoding combinatorially selected hydroxyapatite-binding peptides (HABP) was genetically linked to the 30 end of the open reading frame of green fluorescence protein (GFPuv) and successfully expressed in Escherichia coli. The fluorescence and binding activities of the bi-functional proteins were characterized by, respectively, using fluorescence microscopy and quartz crystal microbalance spectroscopy. The utility of GFPuv-HABP fusion protein was assessed for both time-wise monitoring of mineralization and the visualization of the mineralized tissues. We used an alkaline phosphatase-based reaction to control phosphate release, thereby mimicking biological processes, to monitor calcium phosphate mineralization. The increase in mineral amount was observed using the fusion protein at different time points. GFPuv-HABP1 was also used for efficient fluorescence labeling of mineralized regions on the extracted human incisors. Our results demonstrate a simple and versatile application of inorganic-binding peptides conjugated with bioluminescence proteins as bi-functional bioimaging molecular probes that target mineralization, and which can be employed to a wide range of biomimetic processing and cell-free tissue engineering. Biotechnol. Bioeng. 2011;108: 1021-1030. (C) 2010 Wiley Periodicals, Inc.
Keywords: hydroxyapatite-binding peptides; green fluorescent protein; mineralization; mineralized tissues; inorganic surfaces; nanobiotechnology; BINDING PEPTIDES; DRUG-DELIVERY; FLUORESCENT PROTEINS; QUANTUM DOTS; ADSORPTION BEHAVIOR; PHAGE DISPLAY; IDENTIFICATION; SPECIFICITY; SURFACE; GROWTH; Biotechnology & Applied Microbiology